2020
DOI: 10.1088/2053-1591/ab96f5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cap layer on the properties of AlN barrier HEMT grown on 6-inch Si(111) substrate

Abstract: A series of AlN/GaN heterostructures were grown on 150 mm Si substrates by metal organic chemical vapor deposition (MOCVD). Different cap layer structures, including gallium nitride (GaN) and silicon nitride (SiN x ), were used to passivate the heterostructure surface. A 3.5 nm thick SiN x cap is able to maintain the two dimensional electron gas (2DEG) stability in a long period. An AlN/GaN heterostructure with a 4.5 nm thick AlN barrier exhibits the best 2DEG properties, in terms of sheet resistance, carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this work Nitrogen ion implantation is used to partially block the electrons in the 2DEG region to convert the D-Mode device into an E-Mode device [49]. The conduction bandgap energy level shows whether the device is in D-Mode or E-Mode condition based on the quantum well position concerning the Fermi level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work Nitrogen ion implantation is used to partially block the electrons in the 2DEG region to convert the D-Mode device into an E-Mode device [49]. The conduction bandgap energy level shows whether the device is in D-Mode or E-Mode condition based on the quantum well position concerning the Fermi level.…”
Section: Resultsmentioning
confidence: 99%
“…The GaN cap layer helps to enhance channel mobility by scattering channel electrons. Device breakdown voltage can be improved by reducing the peak electric eld at the drain side with the help of the GaN cap layer [42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of introducing a thin Aluminum Nitride spacer layer is also investigated [25]. Aluminum Nitride spacer layer induced to the simultaneous progress in electron density and mobility as well offers performance of the transistor [26]- [27] in positive manner.…”
Section: J Effect Of Variation In Aluminum Nitride Nucleation Layermentioning
confidence: 99%
“…Several experimental studies have reported the suitability of an in situ SiN x cap layer for preventing the formation of meandering channels, which improves device reliability [10,15]. The in situ SiN x cap layer is used to passivate the surface to suppress the barrier relaxation and neutralize the surface state charge, resulting in a higher 2DEG density [10,11,[15][16][17]. While the concept of an in situ SiN x cap layer seems promising, the realization of in situ SiN x is challenging and demands careful optimization of growth techniques, as both the composition and thickness can affect long-term 2DEG stability [17].…”
Section: Introductionmentioning
confidence: 99%